HASIL PEMERIKSAAN TELUR SOIL TRANSMITTED HELMINTH MENGGUNAKAN CAMPURAN PEWARNA ALAMI DARI DAUN MIANA DAN KULIT BUAH NAGA - acivrida mega charisma; Rio Prasetyo (Klinikal Sains : Jurnal Analis Kesehatan, 2024)
The simplest method for checking worm eggs is by a native technique using a 2% eosin reagent. Eosin itself has properties that are not easily decomposed, causing hazardous and easily flammable waste. Hence, an alternative staining method is needed, environmentally friendly, using natural materials, such as natural dye substances. This research aims to understand the depiction of results in examining Soil Transmitted Helminth (STH) eggs using mint leaves and dragon fruit skin as alternative reagents. The research method involves examining feces using a direct method (wet preparation) to detect worm eggs in feces directly using a 2% Eosin solution. The comparison results between dragon fruit peel extract concentration using aquadest, tested with SPSS analysis version 20 using the Kruskal-Wallis method with a significance value of 0.09 â‰¥ 0.05, indicating significantly different research outcomes. Thus, it can be concluded that there is no difference in staining quality compared to the control. The conclusion drawn from this study is that there's no difference in staining worm egg suspensions using mint leaf extract. This is evident as when observing the worm egg suspension using mint leaf extract, the worm eggs were not clearer, unlike with dragon fruit skin and miana.